RANCANG BANGUN MESIN PENGHANCUR BONGGOL JAGUNG UNTUK INDUSTRI KECIL DENGAN PENGGERAK MOTOR LISTRIK - Satrio Dwi Anggoro (2023)
The rest of the processing of the agricultural industry in corn will produce waste in the form of corn cobs, the amount of which will continue to increase in line with the increase in production capacity. The increase in corn agricultural production in this case must be accompanied by further efforts in the form of management, preservation and use of corncob waste material that has been produced does not reduce environmental aesthetics or does not cause environmental pollution. Therefore, one of the creative ideas in reducing the volume of corncob waste and increasing its added value is to utilize corncob waste to be turned into fish feed by first going through a refining process using a crusher. The method used in this research is by conducting literature studies, field studies, concept design processes, selection of manufacturing processes, manufacturing processes, trials, and formulation of results. The corncob crusher machine that has been made has dimensions (LxWxH) 813 x 392 x 870 mm. With several main components, namely frames, in and out hoppers, hammer mills, filters, and driving motors. The main drive of this corncob crusher machine is an electric motor with a power of 1 hp, and the rotation of the machine is channeled through the pulley and belt. The pulley measures 3 inches for the driven pulley and 4 inches for the driven pulley, and the belt is 1.138 m long. And the result of the machine that the author has made has a crushing capacity of 3 Kg/hour consisting of 1.2 kg/hour for 1-2 mm flour sizes and 1.8 kg/hour for 3-5 mm sizes.